2008
DOI: 10.1007/s12098-008-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and bone mineralization in patients with juvenile idiopathic arthritis

Abstract: Early diagnosis and suppression of disease activity is important in prevention of osteoporosis and growth retardation in children with JIA. BMD has to be measured yearly in patients for accurate diagnosis of osteoporosis. Vitamin D and Ca-rich nutrition with promotion of physical activity and controlled use of steroids may protect the children against bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In adult patients previously diagnosed with juvenile idiopathic arthritis (JIA) Aggarwal et al [9] found decreased BMD. These data are confirmed by another study with 30 JIA patients [10] -with mostly patients from the polyarticular group -suffering from low BMD. The authors did not find a statistic significance for disease duration, but BMD and Z score were associated with lower insulin-like growth factor I (IGF-I) levels, maybe as a sign for restricted growth and bone development in these patients.…”
Section: Concerning Juvenile Idiopathic Arthritis -Jiasupporting
confidence: 68%
“…In adult patients previously diagnosed with juvenile idiopathic arthritis (JIA) Aggarwal et al [9] found decreased BMD. These data are confirmed by another study with 30 JIA patients [10] -with mostly patients from the polyarticular group -suffering from low BMD. The authors did not find a statistic significance for disease duration, but BMD and Z score were associated with lower insulin-like growth factor I (IGF-I) levels, maybe as a sign for restricted growth and bone development in these patients.…”
Section: Concerning Juvenile Idiopathic Arthritis -Jiasupporting
confidence: 68%
“…Aggarwal et al [24] found decreased BMD in adult patients previously diagnosed with JIA. Likewise, Okumus et al [25] found lower BMD levels in 30 JIA patients, especially in the polyarticular group. While they did not detect a statistically significant relationship with disease duration, BMD and the Z score were associated with lower insulin-like growth factor I (IGF-I) levels.…”
Section: Discussionmentioning
confidence: 87%
“…Previously chronic illnesses, such as inflammatory bowel disease [36], type 1 diabetes [37], juvenile idiopathic arthritis [38] and solid organ [39] and bone marrow transplantation [40] in children are associated with vitamin D deficiency. On the other hand, vitamin D deficiency or insufficiency may be a consequence of a chronic illness that affects vitamin D metabolism or absorption, such as biliary atresia and autoimmune hepatitis [41], chronic kidney disease [42], inflammatory bowel disease [36], or cancer [43].…”
Section: Discussionmentioning
confidence: 99%